(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper deals with the concept of faintly (τ_1,τ_2)-continuous functions. Furthermore, some characterizations of faintly (τ_1,τ_2)-continuous functions are investigated. The relationships between faint (τ_1,τ_2)-continuity and other forms of (τ_1,τ_2)-continuity are considered.